The Role of Social Media as A Means of Collaborative Governance in Youth Education - Nafisul Azizah; Aminullah Aminullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid development of digital technology has transformed social media from a platform for entertainment into an important medium for education and information sharing among adolescents. This study aims to analyze the role of social media in supporting collaborative governance for adolescent education. Collaborative governance refers to the cooperation among governments, educational institutions, communities, and other stakeholders in achieving shared educational goals. This research employs a descriptive qualitative approach using literature review and social media content analysis methods. Data were collected from journal articles, online news sources, and educational content available on social media platforms such as YouTube, Instagram, and TikTok.Keywords: social media, collaborative governance, youth education, digital era, digital literacy. The results show that social media significantly contributes to stakeholder collaboration in the dissemination of educational information about drug misuse prevention, digital literacy, mental health awareness, bullying prevention, and character development. Its wide audience, accessibility, and capacity to captivate teenagers with imaginative and engaging material all contribute to its efficacy. However, a number of factors, such as the quality of the information, the regularity of stakeholder collaboration, and the degree of digital literacy among teenagers, affect the effectiveness of collaborative governance through social media. In order to optimize social media's educational potential and guarantee its successful usage as a learning and communication tool for teenagers in the digital age, sustained collaboration among stakeholders is crucial.